Kinesiotherapy and physical activity in COPD and Asthma Patients – A Review - Doroteea Teoibas-Serban; Corneliu-Dan Blendea; Florin Mihaltan (Balneo and PRM Research Journal, 2022)
Background: Obstructive chronic diseases are a continuous challenge for healthcare perfusionists all over the world. Asthma and Chronic Obstructive Pulmonary Disease (COPD) are the most frequent of these diseases. Respiratory or pulmonary rehabilitation started to gain momentum and it is more frequently used to improve muscle strength, cardiac and respiratory endurance and joint flexibility. The objective of this paper is to establish the current programs of physical activity or kinesiotherapy used in the past year and to reveal if there are any gaps or mismatches in the development of the program or in the instruments used to quantify the results of the rehabilitation programs. Materials and methods: We reviewed a total number of 12 articles, randomized control trials using the search words kinesiotherapy, physical therapy, COPD and asthma from the last year on PubMed.gov, from 11 different countries in order to establish which have similar types of exercises, parameters used in order to compare results and which were the outcomes. Results: The final results are positive, although it is hard to determine a unity because there were so many different parameters used to monitor the patients. The most frequent parameter was the 6MWT used to compare the effectiveness of the physical program in 6 studies. Discussion and conclusions: This review had its limitation in comparing the 12 articles researched because of the different number of patients, the various physical activity and rehabilitation exercises used, but especially because of the many varieties of scales and scores used to monitor the effectiveness of the treatment. In order to successfully compare such papers, an international guideline is necessary to relay specific rehabilitation programs for every type of respiratory pathology and also which are the most recommended scales or scores or parameters in general to asses such rehabilitation programs.